Influence of Supporting Electrolyte on Hydroxide Exchange Membrane Water Electrolysis Performance: Anolyte. Issue 8 (26th August 2021) - Kiessling, Aleksandr; Fornaciari, Julie C.; Anderson, Grace; Peng, Xiong; Gerstmayr, Andreas; Gerhardt, Michael R.; McKinney, Samuel; Serov, Alexey; Kim, Yu Seung; Zulevi, Barr; Weber, Adam Z.; Danilovic, Nemanja
Abstract : Hydroxide-exchange-membrane water electrolysis (HEMWE) is an emerging hydrogen-production pathway that combines many advantages of incumbent alkaline water electrolysis (AWE) and proton-exchange-membrane water electrolysis (PEMWE). Advancement in HEMWE has been accelerated with the development of stable and conductive hydroxide exchange membranes (HEMs) and a more comprehensive understanding of alkaline gas-evolving kinetics. However, performance and durability without supporting electrolytes (SELs) remain inferior to PEMWE and AWE and little is known about the role and impact of the SELs. This study investigates the effects of SELs used as anolyte solutions in HEMWEs including cation-type, anion-type, SEL conductivity and pH, presence of carbonates and increased cation/OH − ratios on cell voltage and stability. We report our findings that (i) cell potential and high-frequency resistance did not correlate with anolyte SEL conductivity, (ii) cation-type influences cell voltage at low current densities (<50 mA cm −2 ) as predicted by half-cell measurements, (iii) increased cation/OH − ratio causes increased overpotentials, and (iv) carbonates are exchanged in the HEM but removed via self-purging at high current density. Overall, this study concludes that concentrated KOH is still the best SEL.